2012
DOI: 10.1186/1471-2334-12-191
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism-specific PCR enhances the diagnostic performance of American tegumentary leishmaniasis and allows the rapid identification of Leishmania species from Argentina

Abstract: BackgroundThe diagnosis of the leishmaniases poses enormous challenges in Argentina. The Polymorphism-Specific PCR (PS-PCR) designed and validated in our laboratories has been proven effective for typifying the Leishmania genus from cultured material. Here we evaluated the performance of this method in the diagnosis of American tegumentary leishmaniasis (ATL) and the rapid identification of Leishmania spp. directly from clinical specimens.MethodsA total of 63 patients from northwestern Argentina, with cutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 19 publications
(36 reference statements)
0
47
0
3
Order By: Relevance
“…A fraction from each sample obtained by aspiration, or the scrapings were used for the parasitological diagnosis as described previously, with slight modifications (Marco et al, 2007). Briefly, a search for Leishmania amastigotes was done on smears of the materials, stained with Differential Quick Stain Kit Nº 15 (Biopur Diagnostics, Rosario, Argentina), and examined under a light microscope at the maximum magnification, X 1000 ( Fig.…”
Section: Sampling Methodology and Diagnosis Of Canine Leishmaniosismentioning
confidence: 99%
“…A fraction from each sample obtained by aspiration, or the scrapings were used for the parasitological diagnosis as described previously, with slight modifications (Marco et al, 2007). Briefly, a search for Leishmania amastigotes was done on smears of the materials, stained with Differential Quick Stain Kit Nº 15 (Biopur Diagnostics, Rosario, Argentina), and examined under a light microscope at the maximum magnification, X 1000 ( Fig.…”
Section: Sampling Methodology and Diagnosis Of Canine Leishmaniosismentioning
confidence: 99%
“…Newer DNA-based techniques, like PCR, have a higher sensitivity but are expensive and not widely available. 16,17 Many treatment modalities have been used in CL in pediatric age groups, including topical, systemic, and physical treatments. Intralesional SSG was used in 58 cases, with a cure rate of 84.4% in this study, whereas Zaraa and others 7 and Kharfi and others 11 reported cure rates of 67% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The diseases clinic form in humans depends largely on the etiological agent involved, being Leishmania infantum responsible for Visceral Leishmaniasis (VL), while Leishmania braziliensis, Leishmania amazonensis, Leishmania guyanensis, and Leishmania panamensis are responsible for Tegumentary Leishmaniasis (TL) in Argentina (Marco et al, 2012;PAHO/WHO-SOPERJ, 2008;Salomón et al, 2008a). Additionally, each Leishmania species is transmitted by one or a few species of phlebotomine sandflies (specific or permissive vectors) (Volf and Peckova, 2007), being this parasite-sandfly specific interaction associated to the infectivity and virulence.…”
Section: Introductionmentioning
confidence: 98%